Analysis of the Service Quality of the Social Security Administering Agency (BPJS) at the Merauke Regency Regional General Hospital - Rini Puspita Sari; Nur Jalal; Frederikus Antonius Mana (PAPSEL Research and Consulting, 2024)
BPJS services certainly cannot be separated from efforts to maintain service quality standards which at least include service procedures, completion time, service costs, service products, facilities and infrastructure, as well as the competence of service personnel. Therefore, BPJS as an institution that provides health insurance to the public should measure the quality of services provided, especially through the HIS program. The aim of this research is to describe how the Health Insurance Administering Agency (BPJS) provides services at the Merauke Regency Regional General Hospital (RSUD Merauke Regency). The research method used is a qualitative descriptive technique. Based on the research results, the availability of adequate health facilities and equipment at BPJS counters can help officers in carrying out their duties in providing services to BPJS participants and is a factor that influences services at BPJS counters in Merauke-General Region. the affected hospitals are physical evidence. In accessing health services, officers must be sensitive in handling patient complaints and nursing staff must be responsive in resolving complaints from BPJS participants. Apart from that, nurses or civil servants must be punctual and each have an educational background related to BPJS. This applies to both training in the health and non-health sectors and the last is certainty, namely that to get services from BPJS, patients must follow the procedures set out in regional regulations, do not follow